The Dynamics of T and B Cells in Lymph Node during Chronic HIV Infection: TFH and HIV, Unhappy Dance Partners? - Hong, Jung Joo; Chang, Kyu-Tae; Villinger, Francois (Frontiers in Immunology, 2016)
Although the dynamics of germinal center (GC) formation, TFH cell recruitment to B cell follicles within lymphoid organs and changes of lymphoid tissue architecture in HIV/SIV infection have been documented, the underlying immunopathology remains unclear. Here, we summarize what is known regarding the kinetics of TFH cells and GC B cells during the course of infection as well as the potential immunopathological features associated with structural changes in the lymphoid compartment. This review also explores the implications cell dynamics in the formation and maintenance of viral reservoirs in hyperplastic follicles of secondary lymphoid organs before and after viral suppressive antiretroviral therapy.